Cancer Radiation Therapy May Be Associated With Atrial Fibrillation - Apte, Nachiket; Dherange, Parinita; Mustafa, Usman; Ya'qoub, Lina; Dawson, Desiree; Higginbotham, Kathleen; Boerma, Marjan; Morin, Daniel P.; Gupta, Dipti; McLarty, Jerry; Mansour, Richard; Dominic, Paari (Frontiers in Cardiovascular Medicine, 2021)
Background: The association of atrial fibrillation (AF) with cancer and cancer types is inconclusive. Similarly, data regarding the association of AF with different cancer therapies are controversial. Objectives: To study the association of AF with cancer subtypes and cancer therapies. Methods: We studied all patients aged 18–89 years who presented to the Feist Weiller Cancer Center, with or without a diagnosis of cancer, between January 2011 and February 2016. Electronic health records were systematically queried for baseline demographics and ICD-9 and ICD-10 codes for specific co-morbidities. Patients with a diagnosis of AF were tabulated based on cross-validation with the ECG database and/or by recorded history. We assessed the prevalence and risk of AF based on cancer diagnosis, specific cancer type, and cancer therapy. Results: A total of 14,600 patients were analyzed. Compared to non-cancer patients (n = 6,801), cancer patients (n = 7,799) had a significantly higher prevalence of AF (4.3 vs. 3.1%; p < 0.001). However, following correction for covariates in a multivariable logistic regression model, malignancy was not found to be an independent risk factor for AF (p = 0.32). While patients with solid tumors had a numerically higher prevalence of AF than those with hematological malignancies (4.3 vs. 4.1%), tumor type was not independently associated with AF (p = 0.13). AF prevalence was higher in patients receiving chemotherapy (4.1%), radiation therapy (5.1%), or both (6.9%) when compared to patients not receiving any therapy (3.6%, p = 0.01). On multivariable logistic regression, radiation therapy remained an independent risk factor for AF for the entire study population (p = 0.03) as well as for the cancer population (p < 0.01). Conclusions: Radiation therapy for cancer is an independent risk factor for AF. The known association between cancer and AF may be mediated, at least in part, by the effects of radiation therapy.